2008
DOI: 10.2134/jeq2007.0453
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Balance for Composting Operations

Abstract: The greenhouse gas (GHG) impact of composting a range of potential feedstocks was evaluated through a review of the existing literature with a focus on methane (CH(4)) avoidance by composting and GHG emissions during composting. The primary carbon credits associated with composting are through CH(4) avoidance when feedstocks are composted instead of landfilled (municipal solid waste and biosolids) or lagooned (animal manures). Methane generation potential is given based on total volatile solids, expected volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 56 publications
(85 reference statements)
2
70
0
6
Order By: Relevance
“…The primary benefit of composting is that it reduces CH 4 emissions compared with storage of manure under anaerobic conditions (Brown et al, 2008). However, depending on the intensity of composting, NH 3 losses can be particularly high, reaching up to 50% of the total manure N (Peigné and Girardin, 2004).…”
Section: Compostingmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary benefit of composting is that it reduces CH 4 emissions compared with storage of manure under anaerobic conditions (Brown et al, 2008). However, depending on the intensity of composting, NH 3 losses can be particularly high, reaching up to 50% of the total manure N (Peigné and Girardin, 2004).…”
Section: Compostingmentioning
confidence: 99%
“…Similarly, the aeration of compost reduces CH 4 emissions (Thompson et al, 2004;Jiang et al, 2011b;Park et al, 2011), but can increase NH 3 and N 2 O losses (Tao et al, 2011). However, the review by Brown et al (2008) concluded that, even in a worst-case scenario, the increase in N emissions is minimal in comparison with the benefits associated with the CH 4 reductions.…”
Section: Compostingmentioning
confidence: 99%
“…These emissions are dependent on the technology of the plant and the machinery used such as shredders, front-loaders, turning equipment, screenings and other processing activities. These emissions are beyond the scope of this review but updated information can be found elsewhere (Boldrin et al 2009;Scheutz et al 2009;Lou and Nair 2009;Brown et al 2008).…”
Section: Carbon Dioxide (Co 2 )mentioning
confidence: 99%
“…Greenhouse gases such as methane (CH 4 ) and nitrous oxide (N 2 O) are produced through the treatment of dairy manure (Brown et al 2008;Davidson 2009). Because it is known that CH 4 and N 2 O have strong greenhouse effects ) and 298-fold (N 2 O) greater than the greenhouse effects of CO 2 over a 100-year time horizon; IPCC 2007], and N 2 O is also known to contribute to ozone layer destruction (Ravishankara et al 2009), these gas emissions must be mitigated.…”
Section: Introductionmentioning
confidence: 99%